Utilization of Word-of-Mouth Marketing Strategy in Culinary Business - Eddy Soeryanto Soegoto; Nurul Amelia; Nada Archy Dhafina; Wellga Berlianti (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this study is to analyze how the benefits of the Word of Mouth marketing strategy (word of mouth marketing) are in supporting the improvement of the culinary business. This study used qualitative research methods. The results of this study are the application of the Word of Mouth strategy in the culinary industry sector in increasing sales and building brand awareness and growing public trust in products and companies. The presence of the Word Of Mouth strategy maximizes the development of the culinary business industry with a very wide reach. This study was conducted to determine how effective and influential the use of the Word of Mouth strategy is in the culinary business. In the end, the Word of Mouth marketing communication strategy can be utilized and beneficial for culinary business people in this modern era. Word of mouth marketing communication strategy is very helpful in promoting and attracting potential customers and retaining repeat customers